Two snakebite antivenoms have potential to reduce Eswatini's dependency upon a single, increasingly unavailable product: Results of preclinical efficacy testing. - Stefanie K Menzies; Thea Litschka-Koen; Rebecca J Edge; Jaffer Alsolaiss; Edouard Crittenden; Steven R Hall; Adam Westhorpe; Brent Thomas; James Murray; Nondusimo Shongwe; Sara Padidar; David G Lalloo; et al. (PLoS Neglected Tropical Diseases)
Background Snakebite is a major public health concern in Eswatini, where treatment relies upon one antivenom-SAIMR Polyvalent. Although effective in treating snakebite, SAIMR Polyvalent is difficult to source outside its manufacturing country (South Africa) and is dauntingly expensive. We compared the preclinical venom-neutralising efficacy of two alternative antivenoms with that of SAIMR Polyvalent against the lethal and tissue-destructive effects of venoms from five species of medically important snakes using in vivo murine assays. The test antivenoms were 'Panafrican' manufactured by Instituto Clodomiro Picado and 'PANAF' manufactured by Premium Serums & Vaccines. Principal findings In vivo murine preclinical studies identified both test antivenoms were equally or more effective than SAIMR Polyvalent at neutralising lethal and tissue-destructive effects of Naja mossambica venom. Both test antivenoms were less effective than SAIMR Polyvalent at neutralising the lethal effects of Bitis arietans, Dendroaspis polylepis, Hemachatus haemachatus and Naja annulifera venoms, but similarly effective at neutralising tissue damage induced by B. arietans and H. haemachatus venoms. In vitro immunological assays identified that the titres and toxin-specificities of immunoglobulins (iGs) in the test antivenoms were comparable to that of SAIMR Polyvalent. Plasma clotting disturbances by H. haemachatus and N. mossambica were neutralised by the test antivenoms, whereas SAIMR Polyvalent failed to neutralise this bioactivity of N. mossambica venom. B. arietans SVMP activity was equally reduced by all three antivenoms, and H. haemachatus and N. mossambica PLA2 activities were neutralised by all three antivenoms. Conclusions While both Panafrican and PANAF antivenoms exhibited promising preclinical efficacies, both were less poly-specifically effective than SAIMR Polyvalent in these murine assays. The efficacy of these antivenoms against the lethal and tissue-destructive effects of N. mossambica venom, the most common biting species in Eswatini, identify that Panafrican and PANAF antivenoms offer effective alternatives to SAIMR Polyvalent for the treatment of snakebite in Eswatini, and potentially for neighbouring countries.